Time-lapse photography reveals the occurrence of unexpected bee-pollination in Calanthe izuinsularis, an endangered orchid endemic to the Izu archipelago. Issue 13 (11th April 2017) - Suetsugu, Kenji; Nakahama, Naoyuki; Ito, Azusa; Isagi, Yuji
ABSTRACT: Calanthe izuinsularis is a rare, beautiful and fragrant orchid endemic to the Izu archipelago. Although it is known that mainland populations of closely related Calanthe species are pollinated by medium- to large-sized bees, it is likely that C. izuinsularis has been forced to alter its floral biology to attract alternative pollinators, as large-sized bees are rarely found on the Izu Islands. Indeed, the unusual floral characteristics of C. izuinsularis, which produces pale flowers that emit a strong and fragrant scent during the night, are considered the adaptation to a moth-pollinator syndrome. As expected, our time-lapse photography using a digital camera revealed that the inflorescences of C. izuinsularis were most frequently visited by nocturnal moths such as Noctuidae, Geometridae and Crambidae, which accounted for 50% of all insect visits (in terms of both the number of frames with captured visitors and the number of times visited). However, our study could not provide evidence of a pollinator shift towards moths because none of the moth species was observed with pollinaria. On the other hand, our study found that the pollinaria of C. izuinsularis could become attached to the mesothorax of the small-sized sweat bee Lasioglossum occidens . Therefore, our study suggests that C. izuinsularis is still somewhat dependent on bee pollination, while the orchid has changed its floral colouration and scent. The occurrence of bee-pollination in C. izuinsularis would provide an explanation for how the natural hybridisation between C. aristulifera, C. discolor and C. izuinsularis can occur.